INTRODUCTION TO THE SPECIAL ISSUE ON BLENDED LEARNING - Picciano, Anthony G. (Online Learning, 2009)
In April 2008, the University of Illinois-Chicago hosted the Fifth Sloan-C Workshop on Blended Learning and Higher Education. This workshop attracted 180 educational leaders, faculty members, instructional designers and researchers who discussed, shared and considered effective practices in the design and delivery of blended learning environments. Presentations on best practices, lessons learned, and research on the phenomenon of blended learning stoked the discussion for two days. The theme of the workshop, Blending with Purpose, attempted to focus the discussions on the importance of designing blended learning courses and programs with specific educational goals and objectives in mind. The theme developed out of a growing concern that many faculty were using the latest technology simply for the sake of the using technology without carefully considering the pedagogical benefits and “purpose”. The organizing committee for the workshop also understood that blended learning was not just a faculty-driven activity but needed support and guidance from the administration and instructional designers. As a result, three areas of focus helped organize the workshop activities namely: administration, pedagogy, and evaluation/assessment.